Immune and spermatogenesis-related loci are involved in the development of extreme patterns of male infertility - Cerván-Martín, Miriam (2022)
Funding Information: We thank the National DNA Bank Carlos III (University of Salamanca, Spain) for supplying part of the control DNA samples from Spain and all the participants for their essential collaboration. This work was supported by the Spanish Ministry of Science through the Spanish National Plan for Scientific and Technical Research and Innovation (refs. SAF2016-78722-R and PID2020-120157RB-I00), the Andalusian Plan for Research and Innovation (PAIDI 2020) (ref. PY20_00212), and the R+D+i Projects of the FEDER Operational Programme 2020 (ref. B-CTS-584-UGR20). F.D.C. was supported by the “Ramón y Cajal” programme (ref. RYC-2014-16458), and L.B.C. was supported by the Spanish Ministry of Economy and Competitiveness through the “Juan de la Cierva Incorporación” programme (ref. IJC2018-038026-I, funded by MCIN/AEI /10.13039/501100011033), all of them including FEDER funds. A.G.J. was funded by MCIN/AEI /10.13039/501100011033 and FSE “El FSE invierte en tu futuro” (ref. FPU20/02926). IPATIMUP integrates the i3S Research Unit, which is partially supported by the Portuguese Foundation for Science and Technology (FCT), financed by the European Social Funds (COMPETE-FEDER) and National Funds (projects PEstC/SAU/LA0003/2013 and POCI-01-0145-FEDER-007274). A.M.L. is funded by the Portuguese Government through FCT (IF/01262/2014). P.I.M. is supported by the FCT post-doctoral fellowship (SFRH/BPD/120777/2016), financed from the Portuguese State Budget of the Ministry for Science, Technology and High Education and from the European Social Fund, available through the Programa Operacional do Capital Humano. ToxOmics—Centre for Toxicogenomics and Human Health, Genetics, Oncology and Human Toxicology, Nova Medical School, Lisbon, is also partially supported by FCT (Projects: UID/BIM/00009/2013 and UIDB/UIDP/00009/2020). SLarriba received support from “Instituto de Salud Carlos III” (grant DTS18/00101], co-funded by FEDER funds/European Regional Development Fund (ERDF)—a way to build Europe), and from “Generalitat de Catalunya” (grant 2017SGR191). SLarriba is sponsored by the “Researchers Consolidation Programme” from the SNS-Departament de Salut Generalitat de Catalunya (Exp. CES09/020). The German cohort was recruited within the Male Reproductive Genomics (MERGE) study and supported by the German Research Foundation Clinical Research Unit ‘Male Germ Cells’ (DFG CRU326, grants to F.T. and J.G.). This article is related to the Ph.D. Doctoral Thesis of Miriam Cerván-Martín (grant ref. BES-2017-081222 funded by MCIN/AEI/10.13039/501100011033 and FSE “El FSE invierte en tu futuro”). Publisher Copyright: © 2022, The Author(s).